Pathogenic copy number variants and SCN1A mutations in patients with intellectual disability and childhood-onset epilepsy. Issue 1 (December 2016) - Fry, Andrew; Rees, Elliott; Thompson, Rose; Mantripragada, Kiran; Blake, Penny; Jones, Glyn; Morgan, Sian; Jose, Sian; Mugalaasi, Hood; Archer, Hayley; McCann, Emma; Clarke, Angus; et al.
Abstract Background Copy number variants (CNVs) have been linked to neurodevelopmental disorders such as intellectual disability (ID), autism, epilepsy and psychiatric disease. There are few studies of CNVs in patients with both ID and epilepsy. Methods We evaluated the range of rare CNVs found in 80 Welsh patients with ID or developmental delay (DD), and childhood-onset epilepsy. We performed molecular cytogenetic testing by single nucleotide polymorphism array or microarray-based comparative genome hybridisation. Results 8.8 % (7/80) of the patients had at least one rare CNVs that was considered to be pathogenic or likely pathogenic. The CNVs involved known disease genes (EHMT1, MBD5 andSCN1A ) and imbalances in genomic regions associated with neurodevelopmental disorders (16p11.2, 16p13.11 and 2q13). Prompted by the observation of two deletions disruptingSCN1A we undertook further testing of this gene in selected patients. This led to the identification of four pathogenicSCN1A mutations in our cohort. Conclusions We identified five rarede novo deletions and confirmed the clinical utility of array analysis in patients with ID/DD and childhood-onset epilepsy. This report adds to our clinical understanding of these rare genomic disorders and highlightsSCN1A mutations as a cause of ID and epilepsy, which can easily be overlooked in adults.